THE EFFECT OF WORKLOAD AND TRAINING ON EMPLOYEE PERFORMANCE - Folia, Puspita Silvana Aza Ulmi; Suprapto, Hery (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research was motivated by the decline in employee performance at Tikung Lamongan Islamic Junior High School, which was caused by the large workload and lack of training for employees, so that the task work became less than optimal. This study aims to find out how much workload and training affect employee performance at Tikung Lamongan Islamic Junior High School. The research method uses a quantitative approach. The population in this study is all employees at Tikung Lamongan Islamic Junior High School. The sample used was 50 respondents. The data analysis technique uses multiple linear regression analysis, classical assumption tests, t-tests, f-tests, and realism. Based on the results of the analysis and discussion, it was obtained that workload and training have a significant influence on employee performance partially. From the calculation using multiple linear regression obtained that the workload and training simultaneously and significantly affect employee performance. Keywords: Workload; Training; Employee Performance